Linear multi-electrode arrays for recording population data from the spinal dorsal horn - Greenspon, Charles (2018)
The dorsal horn of the spinal cord is a complex laminar structure integrating exteroceptive signals from the primary afferent fibers into the central nervous system. The laminae of the spinal cord exhibit specialised roles and distinct processes occur across the axes of the dorsal horn. One of the most common in vivo approaches to recording spinal activity is single unit electrophysiology of cells that are believed to be representative of the subjects perception of stimuli. This approach has produced invaluable data but has not progressed in over half a century and fails to account for the specialised processes that occur in each lamina as well as the considerable cellular heterogeneity within and between laminae.